Activating CARD14 Mutations Are Associated with Generalized Pustular Psoriasis but Rarely Account for Familial Recurrence in Psoriasis Vulgaris. - IRVINE, ALAN (My University, 2015)
Caspase recruitment family member 14 (CARD14, also known as CARMA2), is a scaffold protein that mediates NF-κB signal transduction in skin keratinocytes. Gain-of-function CARD14 mutations have been documented in familial forms of psoriasis vulgaris (PV) and pityriasis rubra pilaris (PRP). More recent investigations have also implicated CARD14 in the pathogenesis of pustular psoriasis. Follow-up studies, however, have been limited, so that it is not clear to what extent CARD14 alleles account for the above conditions. Here, we sought to address this question by carrying out a systematic CARD14 analysis in an extended patient cohort (n=416). We observed no disease alleles in subjects with familial PV (n=159), erythrodermic psoriasis (n=23), acral pustular psoriasis (n=100), or sporadic PRP (n=29). Conversely, our analysis of 105 individuals with generalized pustular psoriasis (GPP) identified a low-frequency variant (p.Asp176His) that causes constitutive CARD14 oligomerization and shows a significant association with GPP in Asian populations (P=8.4×10(-5); odds ratio=6.4). These data indicate that the analysis of CARD14 mutations could help stratify pustular psoriasis cohorts but would be mostly uninformative in the context of psoriasis and sporadic PRP.
PUBLISHED
Keywords: CARD14